(untitled) (Research, Society and Development, 2021)
The teaching of mathematics requires from the teacher methods that reach all students and make them an active subject in learning, it is up to the teacher to find ways to facilitate the process of acquiring knowledge. Based on this, the objective is to seek to disseminate the Theory of Semiotic Representation Records developed by the Frenchman Raymond Duval and present his contributions to the teaching of functions. This research is of a qualitative nature and is configured as a bibliographic survey where the studies of Raymond Duval were used. The two main research topics are: the theory of semiotic representation records, where Duval’s career, his contribution to the Mathematics Teaching Research Institute - IREM and his theory are discussed. The second topic, teaching function according to Duval’s theory, presents the use of his theory in teaching function and the types of approach to this content. Thus, the global interpretation of figurative properties approach is the most efficient and allows to increase the student’s potential.